Integrative neuromuscular training in youth athletes. Part II: Strategies to prevent injuries and improve performance - Fort-Vanmeerhaeghe, A.; Romero-Rodriguez, D.; Lloyd, R. S.; Kushner, A.; Myer, G. D. (Strength and Conditioning Journal, 2016)
The second part of this review provides a flexible approach to integrative neuromuscular training (int) with the goals to improve injury resilience and to enhance sport and motor performance abilities in youth populations. The proposed model of int in this manuscript presents 6 essential components: dynamic stability (lower limb and core), strength, plyometrics, coordination, speed and agility, and fatigue resistance. The development of these 6 capacities are integral in establishing an important foundation by initially developing fundamental movement skill competency before building upon these skills to enrich sports-specific and activity-specific skill sets.